‘…SOME OF THEM CRUSHED AND PERISHING UNDER THE WEIGHT OF THE BUILDINGS PRESSING UPON THEM’. THE EARTHQUAKE IN CARNUNTUM - COIN FINDS IN ARCHAEOLOGICAL CONTEXT - Cristian Anton Gazdac; Franz Humer; Andreas Konecny (Journal of Ancient History and Archaeology, 2015)
<span style="line-height: 107%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The present study presents the connection between the earthquakes and the Roman coinage from iconography to relief funds from the state. The main part is dedicated to the case of the ‘civilian’ settlement of Carnuntum in Pannonia Superior (nowadays, Petronell-Carnuntum, Austria). The archaeological excavations and the coin finds related to the pre- and post-earthquake phases reveal the way the Romans have reconstruct/repair the edifices after this event at the mid-4th century AD.